Rachunek kosztów jako podstawa budżetowania i kontroli kosztów w zakładzie opieki zdrowotnej - Kogut, Joanna (The Cost Accounting of as the Basis for Cost Budgeting and Cost Control in a Medical Health Care Enterprise, 2006)
Managing a medical health care enterprise in the changing conditions of health insurance system undergoing reforms requires an application of new, effective management methods and tools. Budgeting is one of such methods. However, in order to be able to implement it and carry it out effectively it becomes indispensable to introduce modern cost accounting system, which would constitute the information basis of budgeting and costs control processes. New solutions in this field should be directed towards an improvement of management, proper allocation of resources among particular centers, as well as the analysis of unit costs related to performed services with reference to prices of these services functioning at the market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 166-174